Comparison of Graphitic Carbon Nitrides Synthetized from Melamine and Melamine-Cyanurate Complex: Characterization and Photocatalytic Decomposition of Ofloxacin and Ampicillin - Praus, Petr; Smýkalová, Aneta; Foniok, Kryštof (Materials (Basel, Switzerland), 2021)
Graphitic carbon nitride (g-C3N4, hereafter abbreviated as CN) was prepared by the heating of melamine (CN-M) and melamine-cyanurate complex (CN-MCA), respectively, in air at 550 °C for 4 h. The specific surface area (SSA) of CN-M and CN-MCA was 12 m2 g-1 and 225 m2g-1 and the content of oxygen was 0.62 wt.% and 1.88 wt.%, respectively. The band gap energy (Eg) of CN-M was 2.64 eV and Eg of CN-MCA was 2.73 eV. The photocatalytic activity of the CN materials was tested by means of the decomposition of antibiotics ofloxacin and ampicillin under LED irradiation of 420 nm. The activity of CN-MCA was higher due to its high SSA, which was determined based on the physisorption of nitrogen. Ofloxacin was decomposed more efficiently than ampicillin in the presence of both photocatalysts.
Keywords: graphitic carbon nitride; ampicillin; melamine; ofloxacin; photocatalysis; melamine-cyanurate complex